TSC2/PKD1 contiguous deletion syndrome in a pregnant woman: A case report - Huang, Shaofang; Xu, Kangxiang; Xu, Yuqi; Zhao, Lu; He, Xiaoju (Frontiers in Medicine, 2023)
TSC2/PKD1 contiguous gene deletion syndrome is a disease caused by the deletions of the TSC2 and PKD1 genes. This is a rare contiguous genomic disease with clinical manifestations of tuberous sclerosis and polycystic kidney disease. To our knowledge, this case report is the first known case of TSC2/PKD1 contiguous gene deletions in a pregnant woman. The patient had multiple renal cysts, angiomyolipoma, hypomelanotic macules, shagreen patch, subependymal giant cell astrocytoma, multiple cortical tubers, and subependymal nodules. The patient underwent genetic testing. To exclude genetic defects in the fetus, prenatal fetal genetic testing was performed after obtaining the patient’s consent. We found an increasing trend in the size of renal cysts and renal angiomyolipomas in patients with polycystic kidney with tuberous sclerosis during pregnancy. Through enhanced clinical monitoring of patients and prenatal genetic testing of the fetus, timely and effective clinical intervention for the mother may be achieved, thus obtaining the best possible outcome for both mother and fetus.